Development Of Flashcard Learning Media With Augmented Reality (AR) On Plant-Based Ingredients At Culinary Vocational School - Anistian Nur Azizah; Febriani Lukitasari; Luthfiyah Nurlaela; Diwyacitta Antya Putri (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The use of learning media will help educators in delivering learning materials so that they can be well understood by students. However, in culinary learning, especially in the material of plant-based food cuts, the learning media used is still dominated by conventional learning methods such as lectures. The media cannot be used to visualize the shape and technique of the pieces in the material, this causes students to tend to be passive and less interested in understanding the material presented. Thus, innovative and interactive learning media is needed to improve students' understanding. Augmented Reality (AR) was chosen as a solution because it is able to display real visuals in 3D so as to help students understand the material visually and realistically. This research aims to develop flashcard learning media with Augmented Reality (AR) on plant-based food ingredient materials, to determine the feasibility of the material and the feasibility of the media for the learning media that has been developed. The type of research and research model used is ADDIE, but the research is limited to the development stage. The subjects of this study are class X students totaling 34 students, while the object of this study is flashcard learning media with augmented reality (AR). The instruments used in this study include validation sheets of material experts and media experts on the media used. The results of this study were concluded that flashcard media with AR is in the form of printed products that include material cut from plant-based foodstuffs, the results of the material validation show a feasibility value of 91% which is included in the very feasible category. Media validation obtained an average score of 97% with a very decent category.